Signification de la concentration de lactate plasmatique au cours de l`exercice - Péronnet, F. (Movement & Sport Sciences - Science & Motricité, 2013)
During short duration exercise, anaerobic glycolysis is a major source of energy and plasma lactate concentration increases from the beginning to the end of exercise (~20 à 30 mmol/L) reflecting large accumulations of lactate. The higher the plasma lactate concentration the better in terms of performance. During prolonged exercise plasma lactate concentration is stable but can be also very elevated (~10 mmol/L). This does not reflect production of anaerobic energy: it is the marker of the error signal needed to stimulate mitochondrial respiration. Plasma lactate concentration increases with workload and also when O2 supply is reduced. For a given workload, the lower the plasma lactate concentration, the better in terms of endurance performance.